Physical Simulation of Individual Heat-Affected Zones in S960MC Steel - M. Mičian; J. Winczek; D. Harmaniak; R. Koňár; M. Gucwa; J. Moravec (Archives of Metallurgy and Materials, 2020)
This research is focused on the analysis of heat-affected sub-zones in 2 mm thick steel S960MC samples, with the aim of observing and evaluating the mechanical properties after exposure to temperatures corresponding to individual heat-affected sub-zones. Test samples were prepared using a Gleeble 3500 thermo-mechanical simulator. The samples were heated in the range from 550°C to 1350°C and were subsequently quickly cooled. The specimens, together with the base material, were then subjected to tensile testing, impact testing, and micro-hardness measurements in the sample cross-section, as well as evaluation of their microstructure. Fracture surfaces are investigated in samples after impact testing. The heat-affected sub-zones studied indicate high sensitivity to the thermal input of welding. There is a significant decrease in tensile strength and yield strength at temperatures around 550°C.